Impacted gutkha presenting as an intrabronchial mass lesion leading to post-obstructive pneumonia. (2022) - Bhardwaj, Swati; Chung, Paul A.; Nigdelioglu, Recep; Reid, Michal; Lockhart, Monica; Forsythe, Sean M.; Ananthanarayanan, Vijayalakshmi
Abstract: A 66-year-old man presented with a chief complaint of difficulty breathing and productive cough. CT scan of the chest revealed an endobronchial mass with associated "tree-in-bud" opacities. A bronchoscopic biopsy of the mass was performed due to clinical suspicion of malignancy. Microscopic examination revealed inflamed endobronchial mucosa, granulation tissue and abundant fragments of uncharacterized organic material, compatible with aspiration. Detailed history revealed a history of chewing "gutkha", a form of smokeless tobacco comprising a mixture of betel nut and other condiments. Microscopic sections of a betel nut and the "gutkha mix" processed subsequently in the histology laboratory were found to be similar to the organic material found in the mass. Thus, a diagnosis of impacted betel nut mixture leading to post-obstructive pneumonia was rendered.